2014
DOI: 10.3168/jds.2013-7243
|View full text |Cite
|
Sign up to set email alerts
|

Rumen bacterial community evaluated by 454 pyrosequencing and terminal restriction fragment length polymorphism analyses in dairy sheep fed marine algae

Abstract: Developing novel strategies to increase the content of bioactive unsaturated fatty acids (FA) in ruminant-derived products requires a deeper understanding of rumen biohydrogenation and bacteria involved in this process. Although high-throughput pyrosequencing may allow for a great coverage of bacterial diversity, it has hardly been used to investigate the microbiology of ruminal FA metabolism. In this experiment, 454 pyrosequencing and a molecular fingerprinting technique (terminal restriction fragment length … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
49
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 41 publications
12
49
1
Order By: Relevance
“…This have been observed by Castro-Carrera et al (2014) who reported that the effect of diet supplementation with marine lipids, evaluated by 454 pyrosequencing, was rather consistent in rumen content or fluid samples despite inherent differences between these fractions in their bacterial composition. However, caution should be taken when the composition of the diets do not differ to a great extent, as occurs in the present study.…”
Section: Quantification Of Microorganisms and Structure And Diversitysupporting
confidence: 60%
“…This have been observed by Castro-Carrera et al (2014) who reported that the effect of diet supplementation with marine lipids, evaluated by 454 pyrosequencing, was rather consistent in rumen content or fluid samples despite inherent differences between these fractions in their bacterial composition. However, caution should be taken when the composition of the diets do not differ to a great extent, as occurs in the present study.…”
Section: Quantification Of Microorganisms and Structure And Diversitysupporting
confidence: 60%
“…This protocol was further used to extract sorghum root and stem mDNA to perform high-throughput pyrosequencing using 16S rRNA marker analysis. Sorghum-associated bacterial communities were shown to be highly diverse, and root and stem communities were significantly different (Castro-Carrera et al, 2014;Lagos et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the effect of tannin extracts on the milk FA profile observed in the present experiment could be due to the modulation of rumen BH because of changes in the microbial ecosystem. Nevertheless, some in vivo studies on rumen bacterial diversity in cows and ewes suggest that B. fibrisolvens and B. proteoclasticus do not play a dominant role in rumen lipid metabolism and that other as-yet-uncultured bacteria phylogenetically classified as Prevotella, Lachnospinaceae incertae sedis, and unclassified Bacteroidales, Clostridiales, and Ruminococcaceae might be more relevant (Boeckaert et al, 2008;Belenguer et al, 2010;Huws et al, 2011;Castro-Carrera et al, 2014). The literature also provides evidence that alterations in rumen outflow of 18-carbon BH intermediates and 18:0 induced by diets based on different types of forages or supplemented with fish oil are not accompanied by significant changes in B. proteoclasticus group (Kim et al, 2008;Huws et al, 2010;Halmemies-Beauchet-Filleau et al, 2013).…”
mentioning
confidence: 99%